The Length of an Infarcted Lesion Along the Perforating Artery Predicts Neurological Deterioration in Single Subcortical Infarction Without Any Relevant Artery Stenosis - Jang, Seong Hwa; Park, Sang-Won; Kwon, Doo Hyuk; Park, Hyungjong; Sohn, Sung-Il; Hong, Jeongho (Frontiers in Neurology, 2020)
Objectives: This study aimed to assess image biomarkers of early neurological deterioration in single subcortical infarction (SSI) without any relevant artery stenosis. Methods: Between June 2005 and December 2009, consecutive patients with SSI within 24 h of symptom onset were enrolled. Magnetic resonance angiography of the brain and neck was obtained from all patients to confirm the absence of any stenosis of relevant arteries. We defined early neurological deterioration (END) as neurological worsening by ≥ 2 points based on the initial National Institutes of Health Stroke Scale score during the first week post admission or prior to hospital discharge. A multiple logistic regression analysis was used to evaluate the independent predictors of END in SSI. Results: A total of 205 patients (109 males; aged 63.9 ± 11.0 years, range 39–90 years) were enrolled, of whom 158 (77%) remained stable or improved, while 47 (23%) showed neurological worsening. There were significant differences in the maximum diameter of the largest area on an axial view and in the number of slices showing cerebral infarction on a transverse plane between patients with and without END. A adjusting for age, hypercholesterolemia, hemoglobin, NIHSS on admission and these magnetic resonance imaging characteristics, the occurrence of having three or more slices showing the cerebral infarction on a transverse plane was an independent predictor of END in SSI without relevant artery stenosis (1 vs. 3; OR 14.281; 95% CI 1.76–115.8; p = 0.013, 1 vs. 4; OR 14.04; 95% CI 1.65–119.57; p = 0.016). Conclusion: The longitudinal length of the infarcted lesion along the perforating artery predicts END in cases of acute SSI without any relevant artery stenosis.